Hubungan Pengetahuan Kesehatan Gigi dan Mulut Dengan Status Gingiva Pada Pasien Pemakai Orthodonsi Cekat di Klinik Gigi Swasta - Putri Esa Jamina; Wiworo Haryani; Etty Yuniarly (Journal of Oral Health Care, 2018)
Knowledge of dental and oral health includes 4 items: maintaining healthy teeth and mouth, consuming the right foods, avoiding bad habits, and using fluorine. The fixed orthodontics consist of a bracket attached to the tooth and used for a long time, so the tooth is very difficult to clean and often has gingival inflammation or gingivitis. To determine the relationship between dental and oral health knowledge with gingival status on fixed orthodontic users in private dental clinics. The type of research used was observational with cross sectional design. Sampling technique is by purposive sampling. The study time lasted from October to November 2017 at a private dental clinic. The instrument of this research is questionnaire and format of examination of gingival status. Data were analyzed using Kendall Tau Correlation test. The level of knowledge of respondents with high category is 75%, gingival status of respondents with healthy category is 60% and the number of respondents who have high knowledge with healthy gingival status is 71.1%. The result of statistical test using correlation test of Kendall Tau known significance value (p) 0.003 then the value is smaller than ? = 0,05 (p <0,05). Oral and dental knowledge is associated with gingival status in fixed orthodontic patients.